THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE ON WORK ENGAGEMENT REMUNERATION DIMEDIATION AND EDUCATOR MOTIVATION - Nurtjahjani, Fullchis; Batilmurik, Ridolof Wenand; Pribadi, Joni Dwi (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study was to analyze the direct effect of transformational leadership on work engagement and the indirect effect mediated by remuneration and educator motivation. This type of research is positivist research. The object of this research is the lecturer at State Polytechnic of Malang. The population in this study amounted to 182 lecturers of Malang State Polytechnic. The sampling technique used census techniques, all populations were used as research samples. The analytical tool used is the Partial Least Square Smart Program (PLS) based on the Variance Based Structural Equation Modeling (SEM) approach. The results show that Transformational Leadership affects Work Engagement, Remuneration does not mediate the effect of Transformational Leadership on Work Engagement, Educator Motivation mediates the Effect of Transformational Leadership on Engagement. Implementation of Remunerationneed to be repaired to meet related to the performance of supporting activities, indirect rewards, research performance, the performance of teaching/lectures, the performance of community service. Future researchers are expected to research teaching staff at all levels of office.